PENERAPAN AKUNTANSI LINGKUNGAN DALAM PENGELOLAAN BIAYA LIMBAH PADA PTPN IV UNIT BAH BUTONG : Akuntansi Lingkungan - Sari, Purwita (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to determine the suitability of the implementation of environmental accounting in PTPN IV Unit Bah Butong with the basic framework of PSAK 1 of 2013 and to determine the obstacles of environmental accounting as a form of social responsibility to the community, especially in waste management and the environment. Data collection techniques are carried out through direct observation, interviews and documentation. The analysis method used in this study is descriptive comparative, meaning that researchers describe the findings of the data obtained. Based on the results of the study, it can be concluded that (1) PTPN IV Unit Bah Butong is in accordance with PSAK No. 1 of 2013 paragraphs 82 and 94, correctly recognized for waste management cost items and waste processing cost measurements in accordance with PSAK No. 1 of 2013 paragraphs 99 and 101 where in the presentation of waste processing costs PTPN IV Unit Bah Butong is in accordance with a clear presentation in the financial position. PTPN IV Bah Butong Unit should create its own account for all activities related to waste management costs, so that the company knows how much the costs are covered for the waste management.